4‐Amino‐1‐Butyl‐1, 2, 4‐Triazolium Nitrate – Synthesis and Characterization. Issue 9 (26th August 2019) - Schaller, Uwe; Keicher, Thomas; Weiser, Volker; Hürttlen, Jürgen
Abstract: An improved synthesis of the energetic ionic liquid 4‐amino‐1‐butyl‐1, 2, 4‐triazolium nitrate (C4 N) is presented via a one‐step metal‐free route using butyl nitrate. C4 N offers promising properties like very low vapour pressure combined with good insensitivity. In addition, long‐term and thermal stability were investigated. The potential use as an energetic additive to improve the rheological properties of GAP‐based energetic polymers was studied resulting in an almost four times lower viscosity at 15 wt.‐% C4 N content. As an additive to a nitromethane‐based monopropellant C4 N works as burning rate modifier which additionally reduces the propellant sensitivity. Abstract :